Stability analysis of leptospirosis compartmental model with impact of contaminated environment - Sooryadas, Mohandas; Haseena, Abdul Latheef; Selsha, Selvan; Balachandran, Krishnan (Nonlinear Analysis: Modelling and Control, 2025)
The main objective of this article is to analyse the stability properties of a model involving humans, animals and contaminated environment. As a first step, the model is formulated, and its biological well-posedness is proved. Then the basic reproduction number is derived using the next generation matrix (NGM) method. The local and global asymptotic stability of the system at the disease free and endemic equilibrium points are also established. Finally, numerical simulations to illustrate the validity of the theoretical results are performed.